Pathogen-triggered metabolic adjustments to potato virus Y infection in potato - Manasseh, Richard; Berim, Anna; Kappagantu, Madhu; Moyo, Lindani; Gang, David R.; Pappu, Hanu R. (Frontiers in Plant Science, 2023)
Potato (Solanum tuberosum L) is affected by several viral pathogens with the most economically damaging being potato virus Y (PVY). At least nine biologically distinct variants of PVY are known to attack potato, with necrotic types named PVYNTN and PVYNWilga being the most recent additions to the list. So far, the molecular plant-virus interactions underlying this pathogenicity are not fully understood. In this study, the response of PVY-resistant cultivar Premier Russet, and susceptible cultivar Russet Burbank to three strains of PVY, PVYNTN, PVYNWilga, and PVYO, was investigated at the metabolome level. The analysis uncovered several common and strain-specific metabolites that are induced by PVY inoculation. In Premier Russet, the major overlap in differential accumulation was found between PVYNWilga and PVYO. However, the 14 significant pathways occurred solely due to PVYNWilga. In contrast, the main overlap in differential metabolite profiles and pathways in Russet Burbank was between PVYNTN and PVYO. Overall, limited overlap was observed between PVYNTN and PVYNWilga. As a result, PVYNWilga-induced necrosis may be mechanistically distinguishable from that of PVYNTN. Furthermore, 10 common and seven cultivar-specific metabolites as potential indicators of PVY infection and susceptibility/resistance were identified by using PLS-DA and ANOVA. In Russet Burbank, glucose-6-phosphate and fructose-6-phosphate were particularly affected by strain–time interaction. This highlights the relevance of the regulation of carbohydrate metabolism for defense against PVY. Moreover, host responses to PVY include metabolite changes that are strain- and cultivar-dependent. Consequently, engineering broad-spectrum resistance may be the most effective breeding strategy for managing these necrotic strains of PVY.